2007
DOI: 10.1038/sj.ijir.3901587
|View full text |Cite
|
Sign up to set email alerts
|

Tunica repair with acellular bladder matrix maintains corporal tissue function

Abstract: Penile conditions, such as Peyronie's disease or tumor resection may require surgical reconstruction of the tunica albuginea. Various materials have been proposed, as a biomaterial for tunica albuginea repair, however, little functional data are available. We examined the applicability and functional outcome of a collagen-based matrix derived from the bladder (acellular bladder matrix (ABM)), as a biomaterial for tunica repair. Biocompatibility testing was performed on the matrix, which included mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Moreover, BAMGs exhibit good biocompatibility and support 67 tissue regeneration [9], and several studies have indicated that 68 BAMG is a suitable scaffold for bladder reconstruction [6,10,11]. 69 In addition, BAMGs have also been shown to prevent permeation 70 of luminal contents into the abdominal cavity [12]. Although mul-71 tilayered urothelial tissues have been shown to be generated by 72 implantation of a simple BAMG scaffold in the bladder, these dense 73 and smooth BAMGs cannot promote satisfactory smooth muscle 74 regeneration, vessel formation, and nerve tissue regeneration, par-75 ticularly for seeding cells or host tissue penetration into the scaf-76 fold [10,13].…”
mentioning
confidence: 98%
“…Moreover, BAMGs exhibit good biocompatibility and support 67 tissue regeneration [9], and several studies have indicated that 68 BAMG is a suitable scaffold for bladder reconstruction [6,10,11]. 69 In addition, BAMGs have also been shown to prevent permeation 70 of luminal contents into the abdominal cavity [12]. Although mul-71 tilayered urothelial tissues have been shown to be generated by 72 implantation of a simple BAMG scaffold in the bladder, these dense 73 and smooth BAMGs cannot promote satisfactory smooth muscle 74 regeneration, vessel formation, and nerve tissue regeneration, par-75 ticularly for seeding cells or host tissue penetration into the scaf-76 fold [10,13].…”
mentioning
confidence: 98%
“…The matrix has been shown to be biocompatible [24][25][26], is processed easily, and has good tissue-handling characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Each type of biomaterials has desirable traits which are exclusive of the other. Acellular tissue matrices possess the desired biocompatibility (11)(12)(13), contain biomimetic factors (14)(15)(16)) that promote tissue development and have adhesion domain sequences (e.g., RGD) that may assist in retaining the phenotype and activity of many types of cells (17). These matrices are known to slowly degrade upon implantation and are usually replaced and remodeled by ECM proteins synthesized and secreted by transplanted or ingrowing cells (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%